The second species of the leafhopper genus Watara Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) - Zhang, Yalin; Yang, Meixia (Zootaxa, 2011)
General characteristics of Watara Dworakowska and a key to known species of the genus are provided. A new species, Watara cordata sp. nov., is described from China.